Mediastinal tumor? - Odriozola, Ernesto (1918)
By one of those coincidences that happen so often in the course of the clinic, he touches us today, opening our work this year, exactly comparable study a patient who served us last year at the same opportunity. If any of the gentlemen who now hear me, saw that sick, continued its evolution and regarded the anatomical parts of it were removed, agree on that almost perfect objective similarity, which makes this a very interesting clinical case example, waking the most lively curiosity and the precise diagnosis is not as easy as one might think. Already in the lesson last year, I said that these cases are not uncommon between us and the speaker had occasion to observe about twenty. The appearance of them is almost always more or less similar, and their death, with one exception, is invariably inexorable, but not worth the possible remedial early diagnosis, and the wonderful advances in surgery.